Associations between Hospital Setting and Outcomes after Pediatric Appendectomy - Anshul Bhatnagar; Sean Mackman; Kyle J. Van Arendonk; Sam Z. Thalji (MDPI AG, 2023)
Prior studies of associations between hospital location and outcomes for pediatric appendectomy have not adjusted for significant differences in patient and treatment patterns between settings. This was a cross-sectional analysis of pediatric appendectomies in the 2016 Kids' Inpatient Database (KID). Weighted multiple linear and logistic regression models compared hospital location (urban or rural) and academic status against total admission cost (TAC), length of stay (LOS), and postoperative complications. Patients were stratified by laparoscopic (LA) or open (OA) appendectomy. Among 54,836 patients, 39,454 (73%) were performed at an urban academic center, 11,642 (21%) were performed at an urban non-academic center, and 3740 (7%) were performed at a rural center. LA was utilized for 49,011 (89%) of all 54,386 patients: 36,049 (91%) of 39,454 patients at urban academic hospitals, 10,191 (87%) of 11,642 patients at urban non-academic centers, and 2771 (74%) of 3740 patients at rural centers (p < 0.001). On adjusted analysis, urban academic centers were associated with an 18% decreased TAC (95% CI −0.193-−0.165; p < 0.001) despite an 11% increased LOS (95% CI 0.087-0.134; p < 0.001) compared to rural centers. Urban academic centers were associated with a decreased odds of complication among patients who underwent LA (OR 0.787, 95% CI 0.650-0.952) but not after OA. After adjusting for relevant patient and disease-related factors, urban academic centers were associated with lower costs despite longer lengths of stay compared to rural centers. Urban academic centers utilized LA more frequently and were associated with decreased odds of postoperative complications after LA.